Neuropeptidergic Systems in Pluteus Larvae of the Sea Urchin Strongylocentrotus purpuratus: Neurochemical Complexity in a “Simple” Nervous System - Wood, Natalie J.; Mattiello, Teresa; Rowe, Matthew L.; Ward, Lizzy; Perillo, Margherita; Arnone, Maria Ina; Elphick, Maurice R.; Oliveri, Paola (Frontiers in Endocrinology, 2018)
The nervous system of the free-living planktonic larvae of sea urchins is relatively “simple”, but sufficiently complex to enable sensing of the environment and control of swimming and feeding behaviours. At the pluteus stage of development, the nervous system comprises a central ganglion of serotonergic neurons located in the apical organ and sensory and motor neurons associated with the ciliary band and the gut. Neuropeptides are key mediators of neuronal signaling in nervous systems but currently little is known about neuropeptidergic systems in sea urchin larvae. Analysis of the genome sequence of the sea urchin Strongylocentrotus purpuratus has enabled the identification of thirty-eight genes encoding neuropeptide precursors (NP) in this species. Here we characterise for the first time the expression of nine of these NP genes in S. purpuratus larvae, providing a basis for a functional understanding of the neurochemical organization of the larval nervous system. In order to accomplish this we used single and double in situ hybridization, coupled with immunohistochemistry, to investigate NP gene expression in comparison with known markers (e.g. the neurotransmitter serotonin). Several sub-populations of cells that express one or more NP genes were identified, which are located in the apical plate, at the base of the arms, around the mouth, in the ciliary band and in the mid- and fore-gut. Furthermore, high levels of cell proliferation were observed in neurogenic territories, consistent with an increase in the number of neuropeptidergic cells at late larval stages. This study has revealed that the sea urchin larval nervous system is far more complex at a neurochemical level than was previously known. Our NP gene expression map provides the basis for future work, aimed at understanding the role of diverse neuropeptides in control of various aspects of embryonic and larval behaviour.